Climate shocks, agriculture, and migration in Nepal: Disentangling the interdependencies - Aslihan Arslan; Eva-Maria Egger; Erdgin Mane; Vanya Slavchevska (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Climate change is expected to increase the risk in agricultural production due to increasing temperatures and rainfall variability. Smallholders can adjust by diversifying income sources, including through migration. Most existing studies investigate whether households send a migrant after experiencing weather shocks, but the literature lacks evidence on migration as an ex-ante measure. In this paper, we disentangle the direct effect of weather shocks on income from agriculture from the effect of changing weather patterns over a few years on migration as a diversification strategy. Using a novel household survey from Nepal combined with 35 years of rainfall and temperature data, we model migration and agricultural production using a simultaneous estimation methodology. The results confirm the simultaneity of these decisions and show that increasing uncertainty in weather patterns and a warming climate increase outmigration in rural Nepal. These results are in line with the hypothesis that migration acts as an income diversification strategy under climate change.
Keywords: F22; O13; O15; Q54; 330; climate change; migration; agriculture; simultaneous estimation; Nepal